Unsteady MHD casson fluid through a porous medium over an inclined plate in the present of chemical reaction - Husna Izzati, Osman; Zulkhibri, Ismail; Nur Fatihah, Mod Omar; Ling, Dennis Chuan Ching; Vieru, Dumitru (Semarak Ilmu Publishing, 2023)
The unsteady of MHD Casson fluid flow through an infinite inclined plate in the presence of chemical reaction is investigated. In this research, Casson fluid model is choose to be used in this study to characterize the non-Newtonian fluid behaviour. We are employed the Laplace transform technique with an appropriate boundary condition to convert the governing partial differential equations into ordinary differential equations. All the transformed equations are then solved numerically by using Mathematica. Finally, we were obtained the exact solution of momentum, energy and concentration of the cases. The results of flow features for different values of the governing parameters, unsteadiness parameter, Casson parameter are analysed in graphs and has been discussed in the result section. The results presented that fluid velocity rises with the increment of magnetic parameter due to the present of Lorentz force. Lorentz force helps in reducing heat for electronic system and radiators. Furthermore, the increasing of inclination angle and chemical reaction make the velocity increases. The result for Casson fluid explained that this fluid helps to lower the resistance of the yield stress so that the velocity become higher.